The potential of music in promoting oracy in students with English as an additional language. (November 2016) - McCormack, Brittany A.; Klopper, Christopher
The ways in which we are able to communicate are, most of the time, dominated through speaking and listening. The ability to speak, listen and understand speech is the basis of oracy; a necessity within society today. The purpose of this study was to examine the interconnectedness of music and language to identify if music can assist in the promotion of oracy in everyday communicative contexts in students who have English as an additional language (EAL). Through the creation of a purpose specific music program, five primary school participants were taught six Western songs, paired with appropriate questions, over a six-week period to determine their oral capacity. Methods within this action research study included observations, informal interviews and graphic melodic contouring. The results indicate that all participants demonstrated an increase in oracy, but to varying degrees, as well as the improvement of pronunciation and vocabulary acquisition. Recommendations for future studies within this area are discussed.